Analysis Of Organizational Culture And The Working Environment On Job Satisfaction Pt. Bank Bjb Area 5 Office With Organizational Commitment Variable Mediator - et. al., Henry Meytra Taufik, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Increasing the conducivity of the work environment by means of a supervisor who creates regular meetings with his subordinates, and on that occasion his subordinates can convey their complaints and their respective perceptions about perceived job satisfaction. This method is expected to make employees more open to their superiors, and feel more cared for so that job satisfaction will be created. Make policies related to employee training and development, which are expected to increase their commitment to the company, because through this training and development employees will be able to increase the knowledge and skills they have to use when working. Increase the intensity of two-way communication, especially those related to work problems, between leaders and subordinates in order to increase employee engagement with the company. The existence of communication makes an employee feel valued and recognized for his existence, so it will be easier for him to feel attached, especially if the employee is given the opportunity to convey what is on his mind. In addition, leaders can also involve their subordinates in making important decisions related to the division in which they work, and this can encourage and train the creativity of everyone. The direct supervisor or in this case the head division, ensures that employees who become subordinates get the facilities. the facilities needed to be able to carry out the job optimally